2021
DOI: 10.1097/opx.0000000000001698
|View full text |Cite
|
Sign up to set email alerts
|

OculoMotor Assessment Tool Test Procedure and Normative Data

Abstract: SIGNIFICANCE:This study establishes normative data and a testing procedure for the oculomotor assessment tool. The oculomotor assessment tool standardizes visual targets for the Vestibular/OculoMotor Screening assessment and provides additional metrics that may aid in the differentiation between those with normal and those with abnormal oculomotor function potentially caused by a concussion.PURPOSE: This study aimed to assess the oculomotor endurance of healthy participants with no self-reported history of con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 55 publications
0
7
1
Order By: Relevance
“…The results of this study provide additional normative data for horizontal and vertical saccades and vergence jumps using the OMAT. Unlike the recent study of Yaramothu et al, 9 we found differences between children and adults and reported the data separately for each group. Statistically significant differences were found between the horizontal and vertical saccades of children and adults.…”
Section: Discussioncontrasting
confidence: 84%
See 4 more Smart Citations
“…The results of this study provide additional normative data for horizontal and vertical saccades and vergence jumps using the OMAT. Unlike the recent study of Yaramothu et al, 9 we found differences between children and adults and reported the data separately for each group. Statistically significant differences were found between the horizontal and vertical saccades of children and adults.…”
Section: Discussioncontrasting
confidence: 84%
“…For both horizontal and vertical saccades examiners used the instructions suggested in a previous publication. 9 “This task will be for 1 minute, look back and-forth between the target ‘X’s’ as fast as you can without overshooting or undershooting the ‘X.’ I will let you know when to stop. Start by looking at left/top green ‘X.” The vergence jumps procedure required the participant to look from a vertical line placed at the “A” point (24 cm) to a near vertical line placed at the “F” point (9 cm) keeping the lines single and clear after every jump vergence movement.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations